Pola Komunikasi Antar Pribadi Magang Merdeka Batch 3 Mahasiswa Prodi Ilmu Komunikasi FIS UNJ - Marisa Puspita Sary; Sutjipto, Vera Wijayanti; Putri, Maulina Larasati; Azzahra, Rahma; Andi Putri Alifiah (LPPM Stikosa - AWS, 2023)
This study discusses the pattern of interpersonal communication between independent interns batch 3 of communication science study program students of FIS UNJ. This study used qualitative methods with primary data collection conducted through interviews. There were 15 informants in the research who were students of Communication Sciences, Faculty of Social Sciences, State University of Jakarta who were participating in the independent internship program batch 3 which was held for five months. The results of this study showed that 15 informants interviewed, 11 of whom felt openness in communication, in empathy communication, 15 informants also experienced the running of the internship program. Meanwhile, 14 out of 15 informants admitted that they felt supportive communication and 14 out of 15 informants said they experienced positive communication in undergoing the independent internship program batch 3.